Moral and scientific boundaries: research ethics on the Thai-Burma border - Parker, J. (Journal of medical ethics, 2012)
The border between Thailand and Burma (Myanmar) is at the forefront of the global battle against malaria, and is an important site for research. The primary reason for this is the fact that it is on the front line in the battle against the development and spread of resistance to antimalarial drugs. That is, it is one of the primary sites of the arms race between the development of new drugs for the treatment of malaria and the evolution of antimalarial resistance in parasites.1 The antimalarial resistance developing here is likely to spread elsewhere. So, much is at stake. Globally, up to a million children each year die from malaria and more than half a billion people are affected.Notwithstanding its global importance, this is a context in which the carrying out of research presents a complex cluster of practical ethical difficulties. One reason for this is that the people who live near the border are mostly migrants or refugees from elsewhere in Burma who have moved to the border area to escape conflict and persecution.2 There are currently thought to be two million Burmese migrants living in Thailand (about 150 000 in refugee camps) and a further million ‘internally displaced’ inside Burma. The people living in the border …